Direct Air Capture of Carbon Dioxide: Advances, Feasibility, and Future Directions - Kuok Ho Daniel Tang (Sustainable Chemical Engineering, 2025)
Direct air capture technologies have gained prominence as vital tools for atmospheric carbon dioxide removal, with four major categories, namely liquid solvent-based, solid sorbent-based, electrochemical, and emerging hybrid systems, demonstrating varying degrees of maturity and feasibility. Liquid solvent-based direct air capture, including systems using potassium hydroxide, amines, and advanced ionic liquids or deep eutectic solvents, benefits from high CO2 reactivity and established chemical regeneration processes, but faces limitations from high thermal energy demands, solvent degradation, and environmental handling concerns. Solid sorbent-based systems, such as those utilizing amine-functionalized materials or metal-organic frameworks, offer low-temperature regeneration and modular designs, yet often suffer from variable adsorption capacity under different humidity levels and degradation over multiple cycles. Electrochemical direct air capture is a rapidly advancing field that uses redox-active materials or ion-exchange membranes to reversibly bind and release CO2 using electrical energy. These systems enable operation under ambient conditions with high selectivity and reduced thermal input, though challenges persist in terms of redox material stability and scalability. Other emerging methods, such as cryogenic, photocatalytic, mineralization-based, and biological direct air capture, offer innovative pathways to reduce energy use or permanently sequester CO2, but remain at early developmental stages. While significant advances have improved energy efficiency, cost-effectiveness, and operational stability across direct air capture technologies, further research is needed to enhance long-term material performance, develop low-cost, scalable reactor designs, and improve integration with renewable energy systems. Future studies should prioritize techno-economic assessments, lifecycle analysis, and hybrid approaches that combine the strengths of multiple direct air capture pathways to achieve cost-effective and durable carbon removal at gigaton scales.